Volume vs. intensity in the training of comsetitive swimmers - Faude, O.; Meyer, T.; Scharhag, J.; Weins, F.; Urhausen, A.; Kindermann, W. (International Journal of Sports Medicine, 2008)
The present study aimed at comparing a high-volume, low-intensity vs. low-volume, high-intensity swim training. In a randomized cross-over design, 10 competitive swimmers performed two different 4-week training periods, each followed by an identical taper week. One training period was characterized by a high-training volume (HVT) whereas high-intensity training was prevalent during the other program (HIT). Before, after two and four weeks and after the taper week subjects performed psychometric and performance testing: profile of mood states (POMS), incremental swimming test (determination of individual anaerobic threshold, IAT), 100 m and 400 m. A small significant increase in IAT was observed after taper periods compared to pre-training (+ 0.01 m/s; p = 0.01). Maximal 100-m and 400-m times were not significantly affected by training. The POMS subscore of "vigor" decreased slightly after both training periods (p = 0.06). None of the investigated parameters showed a significant interaction between test-time and training type (p > 0.13). Nearly all (83 %) subjects swam personal best times during the 3 months after each training cycle. It is concluded that, for a period of 4 weeks, high-training volumes have no advantage compared to high-intensity training of lower volume.